Tumour mutational burden predicts resistance to EGFR/BRAF blockade in BRAF-mutated microsatellite stable metastatic colorectal cancer. (January 2022) - Randon, Giovanni; Intini, Rossana; Cremolini, Chiara; Elez, Elena; Overman, Michael J.; Lee, Jeeyun; Manca, Paolo; Bergamo, Francesca; Pagani, Filippo; Antista, Maria; Angerilli, Valentina; Ros Montaña, Francisco Javier; et al.
Abstract: Aim: To unveil genomic and immunohistochemical expression profiles associated with primary resistance to EGFR/BRAF targeted therapy in patients with BRAF - mutated and microsatellite stable (MSS) metastatic colorectal cancer. Experimental design: In this multicenter case-control study on patients treated with EGFR/BRAF ± MEK blockade, we compared a primary resistance cohort (N = 20; RECISTv1.1 PD/SD, and progression-free survival [PFS] <16 weeks) versus a sensitive one (N = 19; RECISTv1.1 PR/CR, and PFS ≥16 weeks) in terms of clinical and genomic/expression data by means of comprehensive genomic profiling, tumour mutational burden (TMB), BRAF-mutant transcriptional subtypes (BM) classification and PTEN expression. Results: Left-sided tumours (28% of the total) were enriched in the sensitive versus resistant cohort (53% versus 10%, P = 0.010). Genomic alterations in the PIK3CA/MTOR pathway, BM1 status and PTEN loss were similarly distributed among patients with resistant and sensitive tumours. Amplification of CCND1-3 genes were found only in patients with primary resistance (20% versus 0%, P = 0.106). TMB and prevalence of intermediate TMB (TMB-I 6–20 mutations/Mb) were higher in the resistant versus sensitive cohort (median TMB: 6 [IQR, 3–7.29] versus 3 [IQR, 1.26–3.5]; P = 0.013; TMB-I/H: 60% versus 11%; P = 0.001). Patients with TMB-I had shorter PFS (3.3 versus 5.9 months; HR = 2.19, 95%CI, 1.07–4.47, P = 0.031) and overall survival (6.3 versus 10.5 months; HR = 2.22, 95%CI, 1.02–4.81, P = 0.044). Conclusion: Despite the small sample size, the association of a relatively higher TMB with limited benefit from EGFR/BRAF blockade in patients with MSS and BRAF -mutated mCRC deserves prospective validation. Highlights: Primary resistance to BRAF inhibitors in BRAF -mutated metastatic colorectal cancer (mCRC) is as high as 25%. No established biomarkers predict primary resistance. TMB reflects elevated intra-tumour heterogeneity in microsatellite stable (MSS) tumours. Higher TMB is associated with primary resistance to EGFR/BRAF blockade in MSS mCRC. Higher TMB predicts inferior PFS and OS following EGFR/BRAF blockade in MSS mCRC.